TRANSLATING THEORY TO PRACTICE: UNDERSTANDING THE ROLE OF THEORY IN REAL-WORLD BEHAVIOUR CHANGE INTERVENTIONS IN THE PHYSICAL DISABILITY COMMUNITY - Tomasone, Jennifer Rose (My University, 2014)
The purpose of this dissertation was to test the utility of theories across the development, implementation, and evaluation of three nationwide knowledge translation (KT) interventions in the physical disability community. Using a theory-based evaluation guided by the Theory of Planned Behaviour (TPB), Study 1 evaluates the effectiveness of an evidence-based, continuing education module designed to increase emergency health care professionals’ (HCPs) knowledge and use of clinical practice guidelines for managing patients with spinal cord injury (SCI) who present with autonomic dysrefexia. Findings suggest that behaviour change theory should be integrated into the intervention to change theory-based determinants of behaviour, and that information about intervention implementation may help explain observed outcomes. Study 2 examined the use of theory across three phases of research in the Canadian Paralympic Committee’s Changing Minds, Changing Lives (CMCL) intervention. Study 2.1 describes the restructuring of the CMCL curriculum to include research evidence and theory. Study 2.2 evaluates the short- and long-term effects of the CMCL intervention on HCPs’ social cognitions for discussing leisure-time physical activity (LTPA), and explores key implementation variables that predict changes in HCPs’ social cognitions. Overall Study 2 results suggest that: (1) using a KT framework and integrating stakeholders throughout intervention development increases the likelihood that interventionists will adopt and implement the intervention, and (2) real-world implementation is important to understanding intervention effectiveness. Study 3 examines the effectiveness, and its implementation correlates, of Get in Motion (GIM), a nationwide, LTPA-enhancing telephone counseling service for adults with SCI. Study 3 furthers our understanding of the relationship between implementation and effectiveness, and suggests key implementation ingredients that could be targeted in future refinements of GIM. Together, the dissertation studies contribute to our understanding of how to use theory when developing, implementing, and evaluating behaviour change interventions targeting HCPs and other end-users in the physical disability community.
THEORY TO PRACTICE IN THE PHYSICAL DISABILITY COMMUNITY
Keywords: behaviour change; knowledge translation; real-world research; physical disability; leisure-time physical activity; health care professionals